HUBUNGAN TIMBAL BALIK ANTARA KINERJA SOSIAL PERUSAHAAN DAN KINERJA KEUANGAN PERUSAHAAN YANG DIUKUR MENGGUNAKAN PRICE EARNING RATIO - Surya - Wibowo; Juniarti Juniarti Juniarti (Business Accounting Review, 2016)
This study aimed to examine and to prove the reciprocal relationship between corporate social performance and corporate financial performance. Corporate social performance measured by using Sustainability Reporting Index that assessed by using criteria guideliness of GRI G3.1. The corporate financial performance was measured by using Price Earning Ratio. This study also used control variables of leverage and firm size. This research was carried out on go public companies in Indonesia which published sustainability report and listed in GRI’s database with a sample of 80 observations for model 1 and 98 observations for the model 2. The results of this study showed that there was no reciprocal relationship between corporate social performance and corporate financial performance. The results also showed that leverage has negative affect on corporate social performance and corporate financial performance, while firm size did not affect corporate financial performance and corporate social performance.